Urbanization in Kazakhstan: desirable cities, unaffordable housing, and the missing rental market. (1st January 2021) - Seitz, William
ABSTRACT: Kazakhstan's cities are hubs of economic opportunity and prosperity. But despite the Government's ambitious targets, the pace of urbanization remains slow. This study focuses on two key constraints: (i) the very high cost-of-living in Kazakhstan's cities, and (ii) the near absence of a rental housing market outside of the capital, Nur-Sultan. The findings show that the two urban centres of Almaty and Nur-Sultan are 190% and 240% more expensive to live in than the national average. Housing is the primary driver of the disparity: after adjusting for inflation, housing costs tripled in Nur-Sultan and quadrupled in Almaty between 2001 and 2015. As a result, housing costs for the local population in these areas are more unaffordable than famously exclusive cities such as San Francisco and Vancouver. Demand elasticities imply that rural and low-income households are especially unlikely to relocate to high-priced areas where employment prospects are better and average incomes are higher. Regional convergence in wage rates remains slow but appears to be proceeding most quickly in Nur-Sultan, where rental housing is most prevalent. The findings suggest that high rates of home ownership and the high cost-of-living in cities lead to exclusion of lower-income households and restrains economic growth. Highlights Urbanization in Kazakhstan is proceeding very slowly, despite ambitious government targets. The high cost-of-living in the urban areas of Nur-Sultan and Almaty deters many potential domestic migrants. This is driven almost entirely by housing costs: housing in high-demand cities is seriously unaffordable for most people, even among those already living in cities. High home ownership rates and an abnormally small rental market further reduce domestic mobility.